Pengembangan Media Komik Matematika pada Materi Pecahan di SD - Safira, Lubna; Sukmawarti, Sukmawarti (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of this study was to develop a mathematical comic media for fractions in elementary school and to determine the feasibility of comics media. The development model or Research and Development (R&D) carried out in this research is to use a 4-D development model because the stages are clear and briefly describe the development process. The research instrument is a validation sheet from material experts and media experts. The data collection tool used is in accordance with the validity and reliability or consistency to obtain data as a burden in the research using the Questionnaire/ Questionnaire to obtain data about the feasibility of the product. This media is validated by material experts and media experts. After being validated by material experts and media experts, the media was then revised so that the revised media phase I was obtained. The media from the revised phase I was then tested by means of being used by teachers in classroom learning. Media that has gone through the trial process will be revised again. Based on these stages, the final product will be produced Development of Mathematical Comic Media on Fractions in Elementary School. Through the results of media expert validation, it is known that from the 16 questions there are 15 YES assessment categories and 1 NO assessment category. This suggests that media experts state that the Mathematical Comic media is worthy to be studied and used as a medium for learning Mathematics in Fractions material in Mathematics learning.